Experiences in creating a software tool to analyze and postprocess simulated and measured data. (19th September 2018) - Ceraolo, Massimo
Summary: Today, there is a great availability of software to plot simulated or measured data either commercial or free, possibly open source. The author has created one of them, which has the specificity of being compact, compatible with several input formats, and freely distributed, available for Windows, Macintosh, and Unix. It has also the ability to postprocess simulated and measured data. This paper shows some of the choices that have been made to produce this tool, gives hints on their implementation, and shows which special characteristics were searched for, which not always are available on larger tools or tools built into simulation or measuring software.